Assessment of soils stabilized with lignin-based byproducts. (1st December 2018) - Yang, Bo; Zhang, Yang; Ceylan, Halil; Kim, Sunghwan; Gopalakrishnan, Kasthurirangan
Abstract: In this study, biofuel co-products (BCPs) containing lignin derived from biomass were investigated to gain further insight into the effects on stabilizing roadbed soils. A liquid type and a powder type of BCPs were mixed with four types of soils with various contents to determine the mechanical, durability, and microstructural properties of BCP stabilized soils. Results indicated that the addition of BCPs significantly increased soil compressive strength, and both of BCP A and BCP B demonstrated the greater strength improvement on relative coarse soil, such as Soil 4 classified as A-4 or ML. The freeze-thaw durability and moisture susceptibility of soils were improved due to the addition of BCP as well, and Soil 1 classified as A-6 or SC and 3 classified as A-4 or CL-ML obtained more benefit to resist moisture from that. Microstructural analyses using scanning electron microscopy (SEM) and X-ray diffraction (XRD) demonstrated that BCPs are capable to coat and bond soil particles to form strong soil structures. Findings from this study provide a fundamental guidance to pavement researchers and engineers to use BCP as an effective soil stabilizer.